1983
DOI: 10.1042/bj2130485
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an endo-β-galactosidase from Bacteroides fragilis

Abstract: Six strains of Bacteroides fragilis were examined and all found to produce endo-beta-galactosidase, an enzyme that hydrolyses internal beta-galactosidic linkages of oligosaccharides belonging to the poly-N-acetyl-lactosamine series, with the common structure GlcNAc beta 1 leads to 3Gal beta 1 leads to 4GlcNAc/Glc. The enzyme was produced without the addition of an inducer such as keratan sulphate. It was purified 7000-fold from the culture supernatant and obtained with a yield 4-10-fold greater than from sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 33 publications
2
51
0
Order By: Relevance
“…Obviously, the cleavage of terminal macromolecular ß-glycosidically bound Dgalactose is very resistant to most ß-galactosidases, except a few enzymes of bacterial origin. Recently, the endo-ß-galactosidase of Bacteroides fragilis has been shown to hydrolyse internal ß-galactosidic linkages of oligosaccharides belonging to the poly Nacetyl-lactosamine series (18), whereas ß-galactosidase isoenzyme from Turbo cornutus has been described with Substrate specificity towards a ganglioside with terminal ßl->3 linked galactose (20).…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, the cleavage of terminal macromolecular ß-glycosidically bound Dgalactose is very resistant to most ß-galactosidases, except a few enzymes of bacterial origin. Recently, the endo-ß-galactosidase of Bacteroides fragilis has been shown to hydrolyse internal ß-galactosidic linkages of oligosaccharides belonging to the poly Nacetyl-lactosamine series (18), whereas ß-galactosidase isoenzyme from Turbo cornutus has been described with Substrate specificity towards a ganglioside with terminal ßl->3 linked galactose (20).…”
Section: Discussionmentioning
confidence: 99%
“…GBS Type III Capsule Repeating Unit Purification. The GBS cell wall preparation was digested with Escherichia freundii endo-␤-galactosidase (V-Labs, Covington, LA), which specifically recognizes the trisaccharide-repeating unit of the GBS type III CPS backbone and cleaves the ␤1-4 linkage between galactose and glucose residues (28). Cell wall preparation and endo-␤-galactosidase were brought to concentrations of 0.2 M and 10 units͞ml, respectively, in 50 mM sodium acetate (pH 5.5) and allowed to react for 3 days at 37°C in a toluene atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The neutral oligosaccharide and glycopeptide fraction was dissolved in 1 ml H 2 0 and a 50-pl aliquot reduced and radiolabelled using NaB[3H]4 as described previously [14]. The remainder was evaporated in vucuo at 60 "C, dissolved in 0.5 mlO.1 M sodium borate/NaOH buffer (pH 11.3) containing 50 mM NaBH4 and incubated for 16 h at 4°C.…”
Section: H-labelling and Bio-gel P-4 Chromatography Of Oligosaccharimentioning
confidence: 99%
“…An investigation of the specificity of the B. fragilis and E. freundii enzymes using erythrocyte glycolipids as substrates [14] showed that they do not hydrolyse the P-galactosidic linkage at the branch-point of Structure 1, while the P-galactosidic linkage in the corresponding linear sequence lacking the 6-linked N-acetylglucosamine residue is readily cleaved. In a more recent study using desialylated erythrocyte band-3 glycopeptides [9], it was reported that with the E. freundii enzyme the branch-point P-galactosidic linkage can be hydrolysed at high enzyme concentrations, or if the branch-point occurs at the non-reducing end of extended lin-ear sequences containing at least two N-acetyllactosamine with 2 M NaOH and chromatographed on a column units as in Structure 2.…”
mentioning
confidence: 99%